2019
DOI: 10.1093/ecco-jcc/jjz151
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Drug Exposure on Vedolizumab-Induced Endoscopic Remission in Anti-Tumour Necrosis Factor [TNF] Naïve and Anti-TNF Exposed IBD Patients

Abstract: Background and Objectives Vedolizumab has demonstrated efficacy and safety in patients with Crohn's disease [CD] and ulcerative colitis [UC]. Endoscopic outcome data are limited, especially in anti-tumour necrosis factor [TNF] naïve patients. The present study compared endoscopic outcome in anti-TNF naïve and exposed patients, and explored if this was affected by drug exposure. Methods We retrospectively analysed all patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 43 publications
(56 reference statements)
3
23
0
Order By: Relevance
“…The remission rates reported in adult studies are higher than the rates observed in the children in our cohort (17,24), which may be explained by inclusion of anti-TNF refractory PIBD patients only, whereas this was not the case in the adult studies. This is supported by studies showing significantly better outcomes in anti-TNF-naïve IBD patients (25)(26)(27) explanation for loss of response to anti-TNF, our data do not suggest that nonresponse or loss of response to VDZ can be explained by the formation of antibodies to VDZ (28). This is consistent with studies in adults that indicate immunogenicity to occur in <5% of cases (17,29).…”
Section: Discussionsupporting
confidence: 91%
“…The remission rates reported in adult studies are higher than the rates observed in the children in our cohort (17,24), which may be explained by inclusion of anti-TNF refractory PIBD patients only, whereas this was not the case in the adult studies. This is supported by studies showing significantly better outcomes in anti-TNF-naïve IBD patients (25)(26)(27) explanation for loss of response to anti-TNF, our data do not suggest that nonresponse or loss of response to VDZ can be explained by the formation of antibodies to VDZ (28). This is consistent with studies in adults that indicate immunogenicity to occur in <5% of cases (17,29).…”
Section: Discussionsupporting
confidence: 91%
“…Multiple studies in patients with active CD have shown a correlation between VDZ exposure and response, and higher clinical and endoscopic remission rates when stratified by drug exposure. [4][5][6][7][8][9][10] These findings hold out the possibility that dose intensification in patients with low VDZ trough concentrations during induction may result in higher remission rates. In support of this notion, observational data suggest that empiric administration of an additional drug dose in patients with suboptimal response to induction may improve outcomes.…”
Section: Introductionmentioning
confidence: 67%
“…Multiple studies in patients with active CD have shown a correlation between VDZ exposure and response, and higher clinical and endoscopic remission rates when stratified by drug exposure . These findings hold out the possibility that dose intensification in patients with low VDZ trough concentrations during induction may result in higher remission rates.…”
Section: Introductionmentioning
confidence: 73%
“…Both agents are have lower immunogenicity compared to anti-TNF [50], and the presence of ADA has not been consistently associated with therapy inefficacy in registration trials [122][123][124][125]. Early vedolizumab TLs (mainly at weeks 6 and 14) have been variously associated with clinical remission [101,102], treatment persistence [103], biochemical remission [103][104][105], endoscopic response [126], mucosal healing [104,105] and even histological healing [106]; due to the heterogeneity of assays used, timepoints assessed and outcomes investigated, different threshold concentrations have been proposed. An association between vedolizumab TLs during maintenance periods and treatment outcomes has been reported in multiple observational studies [102,106,107].…”
Section: Therapeutic Drug Monitoringmentioning
confidence: 99%